Physicochemical characterization of leaf extracts from Ocotea lancifolia and its effect against wood-rot fungi. (February 2017) - da Silva, Daniela Thomas; Herrera, René; Batista, Bibiana Fontana; Heinzmann, Berta Maria; Labidi, Jalel
Abstract: This study is designed to evaluate the physicochemical properties and the decay resistance of leaf extracts obtained from a native Brazilian tree Ocotea lancifolia . Ethanol was used to obtain crude extract from milled leaves, which was further partitioned with ethyl acetate and butanol achieving two phenolic-rich fractions. Furthermore, wood veneers were impregnated with crude extract and its fractions (at 1 and 4%), and evaluated against two wood-destroying fungi. Firstly, Fourier transform infrared and thermogravimetric analysis confirmed chemical differences on structure, stability and purity of the evaluated extract samples. Crude extract presented lower total phenolic content (178 mg GAE/g dried sample) and lower antioxidant activity than its fractions. Moreover, the fractions showed 360–405 mg GAE/g dried sample and a high scavenging effect (IC50 < 0.75 mg/mL). Chromatographic analysis revealed the presence of quercetin-derived monoglucosides in all samples, such as quercetin-3- O -rhamnoside (∼20–22% in crude extract and ethyl acetate fraction) and quercetin-3- O -glucoside in butanolic fraction (20.71%). Crude extract and ethyl acetate fraction at 4% were the most effective treatments to reduce the action of two wood-rot fungi (mass loss < 8%). Overall, leaf extracts from O. lancifolia can provide a renewable source of antioxidants and eco-friendly wood preservatives. Highlights: Ocotea lancifolia extract was partitioned and two phenolic fractions were obtained. Quercetin-derived compounds were detected by LC/MS analysis in all tested extracts. The fractions presented higher DPPH and ABTS radical scavenging than crude extract. Ethyl acetate fraction at 4% was able to reduce the fungal attack on wood veneers. Crude extract exhibited some impurities but was effective against wood-rot fungi.